Elevated cell-free mitochondria DNA level of patients with premature ovarian insufficiency - Xing-Yu Zhou; Yi-Zhen Yang; Jun Zhang; Xiao-Fei Zhang; Yu-Dong Liu; Zhe Wang; Shi-Ling Chen (BMC, 2023)
Abstract Background Premature ovarian insufficiency (POI) patients present with a chronic inflammatory state. Cell-free mitochondria DNA (cf-mtDNA) has been explored as a reliable biomarker for estimating the inflammation-related disorders, however, the cf-mtDNA levels in POI patients have never been measured. Therefore, in the presenting study, we aimed to evaluate the levels of cf-mtDNA in plasma and follicular fluid (FF) of POI patients and to determine a potential role of cf-mtDNA in predicting the disease progress and pregnancy outcomes. Methods We collected plasma and FF samples from POI patients, biochemical POI (bPOI) patients and control women. Quantitative real-time PCR was used to measure the ratio of mitochondrial genome to nuclear genome of cf-DNAs extracted from the plasma and FF samples. Results The plasma cf-mtDNA levels, including COX3, CYB, ND1 and mtDNA79, were significantly higher in overt POI patients than those in bPOI patients or control women. The plasma cf-mtDNA levels were weakly correlated with ovarian reserve, and could not be improved by regular hormone replacement therapy. The levels of cf-mtDNA in FF, rather than those in plasma, exhibited the potential to predict the pregnancy outcomes, although they were comparable among overt POI, bPOI and control groups. Conclusions The increased plasma cf-mtDNA levels in overt POI patients indicated its role in the progress of POI and the FF cf-mtDNA content may hold the value in predicting pregnancy outcomes of POI patients.